2011
DOI: 10.15232/s1080-7446(15)30445-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient variability for distillers grains plus solubles and dry matter determination of ethanol by-products

Abstract: Vanness, S. J.; Bremer, V. R.; Klopfenstein, T. J.; Kononoff, P. J.; and Erickson, G. E., "Nutrient variability for distillers grains plus solubles and dry matter determination of ethanol by-products" (2011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 8 publications
(7 reference statements)
0
15
0
7
Order By: Relevance
“…The inhaled gas then gains entry into the blood stream by alveolar diffusion and can exert negative effects within the brain, such as the lesions characteristic of PEM (Gould, 1998). The S content of distillers grains has been reported to vary between 0.3 to 1.7% (Buckner et al, 2011;Kim et al, 2012), which is likely due to differences in the fermentation processes among ethanol plants. However, the variability in the S content of the coproduct is a limiting factor to its inclusion in cattle diets (Klopfenstein et al, 2007); therefore, it would be favorable to find a feed additive to limit H 2 S production, allowing this feedstuff to be fed at greater inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The inhaled gas then gains entry into the blood stream by alveolar diffusion and can exert negative effects within the brain, such as the lesions characteristic of PEM (Gould, 1998). The S content of distillers grains has been reported to vary between 0.3 to 1.7% (Buckner et al, 2011;Kim et al, 2012), which is likely due to differences in the fermentation processes among ethanol plants. However, the variability in the S content of the coproduct is a limiting factor to its inclusion in cattle diets (Klopfenstein et al, 2007); therefore, it would be favorable to find a feed additive to limit H 2 S production, allowing this feedstuff to be fed at greater inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, sulfur content of corn ranges from 0.1 to 0.15% of dry matter (DM), whereas sulfur content of DDGS is usually greater than 0.6%, even greater than 1% . Moreover, the investigation of Buckner et al (2011) showed that variation in sulfur content was the largest for all nutrients tested in DDGS as coefficients of variation within days and across days (within the same ethanol plants) ranged from 3 to 13%. It is noteworthy that the dietary sulfur level for beef cattle recommended by the National Research Council (NRC 2000) is only 0.15% and its maximum tolerable concentration is generally estimated at 0.40%.…”
Section: Doi: 1017221/85/2016-cjasmentioning
confidence: 99%
“…Because of the burgeoning ethanol industry in the United States, distillers grains are becoming a common ingredient in dairy diets. However, numerous surveys have shown that the nutrient composition of distillers grains can be quite variable, depending on the source and other factors (Belyea et al, 1989;DePeters et al, 2000;Spiehs et al, 2002;Buckner et al, 2011). Within a survey, average fat concentrations among distilleries have ranged by as much as 4 percentage units, and within-distillery coefficients of variation have been as high as 12% (Spiehs et al, 2002).…”
Section: Introductionmentioning
confidence: 99%